Determination of the Mathematical Model for Plasma Electronic Coefficients of the Earth’s Ionosphere - Temur, Aseel A.; Ahmed, Ala F.; Ali , Rafid A. (Iraqi Journal of Science, 2023)
In this research, electron coefficients such as total collision frequency (colt/N), total ionization frequency (viz/N), and Power (P/N) for different gases such as (Ar, He, N2 and O2 (in Earth’s ionosphere have been calculated by applying the Boltzmann equation utilizing BOLSIG +, and it has been discovered that there is a significant impact of reducing the electric field (E/N) on electronic coefficients under which (E/N) increases. In addition, influence of (E/N) on electronic coefficients was studied. Reducing the electric field was chosen in the restricted range (1-100) Td, and the electronic coefficients for gases in the limited range (50-2000) km of the Earth’s ionosphere. A positive correlation has been explained between all the plasma electronic coefficients and (E/N) for the four gases. It was found that He gas has higher electronic coefficients than other gases in the Earth’s ionosphere because they have lower electron binding energy.